Public Relations in tourism: the role of Public Relations in terms of promotion of cultural assets in Tigray Region - Mulu, Solomon Shiwabaw (Technium Social Sciences Journal, 2020)
Public Relations concept; It is a distinctive management function aimed at mutual communication, establishing and maintaining connections, and acceptance and understanding between an organization and its employees and target audience. The tourism industry develops rapidly and contributes to the economies of the country. Public relation is an essential feature in the modern socio-economic development of tourism. Public relations ensure the transmission of messages about the attraction of a tourist destination and the transport infrastructure of the accommodation to adapt the tourist budget to the needs and changes of the public, and simultaneously measure the pulse of the target audience and follow their expectations. The objective of this study is to reveal the "Role of Public Relations in terms of Promotion of Cultural Assets of Tigray Region". To achieve the goal, a mixed research method is used. The researcher has used a convenient sampling method for qualitative and quantitative data sample size. In-depth interviews and distributed questionnaires were used as data collection tools. And a combination of these data has been interpreted using a triangulation research design.